Mapping Of The Energy Cascade In The Developing Region Of A Turbulent Round Jet - Yaacob, Mohd Rusdy; Buchhave, Preben; Velte, Clara Marika (Joint Journal of Novel Carbon Resource Sciences & Green Asia Strategy, 2021)
Due to practical limitations for conducting measurements in the most interesting, yet difficult flow regions with high shear and turbulence intensities, developing turbulence has been under-explored. These limitations have impaired the ability to properly test the critical assumptions of existing turbulence theory. This paper describes experimental works for acquiring velocity data points and resolving higher order moments of velocities, which may reveal interesting nonequilibrium features of the flow. The measurements presented herein provide a uniquely accurate measurement database of a canonical high shear and high intensity turbulent flow that can serve as a baseline for further theoretical and modelling developments.